Coupled random PWM technique for dual inverter fed induction motor drive - Syed Munvar Ali; V. Vijaya kumar Reddy; M. Surya Kalavathi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
Dual inverter fed induction motor drives provide more advantages in contrast with other multilevel inverter drives. Coupled PWM techniques provide good standard of output voltage than the decoupled PWM techniques for dual inverter configuration. In this paper analysis of open end winding induction motor by coupled random PWM signals and decoupled SVPWM signals was carried out. Induction motor by random PWM technique generate low acoustic noise and electromagnetic interference to near by systems. The performance evaluation of the drive wss implemented in MATLAB/simulink and the results were presented.